3D QR Code-Based Indonesian Cultural lind Map to Critical Thinking Ability - Sukiana, I Made; Suarjana, I Made; Tegeh, I Made (Universitas Pendidikan Ganesha, 2024)
Learning that still uses the teacher centered method results in students' critical thinking abilities being low. This research aims to develop a 3D learning media for a QR code-based map of Indonesian cultural blindness to improve students' critical thinking skills in class IV elementary school science content that is valid, practical and effective. The type of research is ADDIE model development research. The object of this research is the validity, practicality and effectiveness of the QR code-based 3D learning media for Indonesian cultural blind maps. The subjects of this research are media experts, material experts, practitioners and students. The data collection method uses non-tests with questionnaire instruments and description tests. Data analysis techniques use qualitative and quantitative statistics. The research results obtained validity according to material experts of 4.66 and media experts of 4.54, which is included in the very good category of validity. Based on the practicality test, practitioners obtained a percentage of 96% and student responses were 92% in the very good category. Based on the effectiveness test using Paired Sample T-Test analysis of correlated samples, a significance value was obtained in the Sig column (2-tailed) of 0.000, which means that there is a significant difference in students' critical thinking abilities before and after using the media. It was concluded that the learning media that had been developed were declared valid, practical and effective in improving critical thinking skills, so they were suitable for continuous use in learning activities.